Labour-market institutions and macroeconomic shocks - Yu-Fu Chen; Dennis J. Snower; Zoega Gylfi (Institute for the Study of Labor (IZA), 2002)
Macroeconomic shocks and labour-market institutions jointly determine employment growth and economic performance. The effect of shocks depends on the nature of these intitutions and the effect of institutional change depends on the macroeconomic environment. It follows that a given set of institutions may be appropriate at certain times in some countries while not appropriate elsewhere. We derive a dynamic model of labour demand in which the effect of firing costs on labour demand depends on the macroeconomic environment: When the level of macroeconomic activity is expected to drop and/or the trend rate of productivity growth is small, a rise in firing costs affects mainly (and adversely) the hiring decision and not the firing decision. This makes firing costs harmful when they may appear to be most appropriate. The intuition behind these results is quite straightforward: When managers fear that demand may fall in the future they value the right to fire workers. It follows that by making this option more costly, firing costs reduce the value of workers with adverse consequences for hiring and firing.
Keywords: E32; J23; J24; J54; 330; stochastic demand; hiring and firing; real options; firing costs; Arbeitsmarkttheorie; Schock; Arbeitsmarktflexibilisierung; Kündigung; Theorie